Teachers’ Perception On Project Based Learning Method In Teaching English Lesson - Yunda Walia Shafaa; Sholihatul Hamidah Daulay (Didaktika: Jurnal Kependidikan, 2024)
This research investigates how English teachers at Budi Satrya School view project-based learning. The strategy used in this study to gather data from interviews is qualitative. Next, information was gathered to determine how Budi Satrya School teachers felt about Project Based Learning. The findings demonstrate that the Budi Satrya School students benefited from the teachers' application of project-based learning. Additionally, according to this research, children become self-regulated, motivated, cooperative, critical, and communicative learners when they interact with the actual world. Project-based learning has greater beneficial effects than traditional teaching techniques. Project-Based Learning has many benefits over traditional teaching methods, even though it cannot be used with all selected materials.